Efectes de la pesca d'arrossegament en els sediments dels canyons submarins catalans - Puig, Pere (2014)
Bottom trawling is a nonselective commercial fishing technique whereby heavy nets and gear are pulled along the seafloor, modifying the physical properties of seafloor sediments and altering natural sediment fluxes. Most studies addressing the physical disturbances of trawl gear on the seabed have been undertaken in coastal and shelf environments, where the capacity of trawling to modify the seafloor sediments coexists with high-energy natural processes driving sediment erosion, transport and deposition. Recent studies conducted on the Catalan margin have demonstrated that on continental slopes —where the sediment dynamics is less energetic— the reworking of the deep seafloor by bottom trawling produces periodic resuspension of surface sediments, and ultimately modifies the shape of the submarine landscape over large spatial scales. Trawling-induced sediment displacement and removal from fishing grounds causes the morphology of the deep seafloor to become smoother over time, reducing its original complexity. These results suggest that during the last decades, following the industrialization of fishing fleets, bottom trawling has become an important driver of deep seascape evolution.